Percepção de risco à inundação na cidade de Rondonópolis-MT - Araújo, Wellington Rodrigues de (2018)
This study seeks to understand one of the aspects of the relationship between society and nature: how people perceive the phenomenon of floods. Thus, the central object was analyze if the socioeconomic profile of the population influences their perceptions about the risk of flooding. Therefore, selected dwellers residing as close as possible to the Rio Arareau in part of the central area and the neighborhoods Jardim Paulista and Jardim Brasília. These areas were chosen based on previous studies reporting this event. However, in this study, we also attempted, through the theoretical discussion, to address the concept of perception and risk, social and natural aspects to flood risk, contributing to a better understanding of the relationship between society and nature, through flood processes and their relation with use and land occupation and urban expansion where the main point of the debate understood that floods are natural phenomena that occur independently of human will and has a certain periodicity. In this dynamics the study sought results of the affective and cognitive interactions and ties of the residents with the place to which they reside. The results are presented and discussed on the context of the perception and cognition of the residents residing in the areas of flood risk, converging towards the objective of the study. For this purpose, a form with closed questions related to the socioeconomic profile of the resident and his perception about the flood phenomenon to the residents of these areas were applied for data collectionIn addition, were applied, to data collection, a form with closed questions related to the socioeconomic profile of the resident and on the flood phenomenon.The main results achieved indicate that the majority of the population of these areas coexist with only two minimum wages and have incomplete elementary school, most of them live for more than 20 years in these places and understand and perceive the risk of inundation. In this way listen and seek to know their perceptions from their experiences of life about what happens in the city, above all in neighborhoods, is essential for better public management and contributes to the improvement of living conditions.